Management of Uterine Torsion and Incomplete Cervical Dilatation in A Cross Bred Cow - Bhat, Ghulam Rasool; Nisa, Masrat un; Yousuf, Nahida; Singh, Pawan preet; Parrah, Jalaluddin (The Indian Journal of Animal Reproduction, 2022)
A cross-bred cow presented at a referral hospital of Veterinary Clinical Complex with symptoms of straining and colic associated with uterine torsion and its management with Sharma’s method of detorsion followed by medical intervention for cervical dilation is reported.